From FM to TikTok: a mixed-methods study of platform gaps, content misalignment, and rural–urban divides in Jordanian university radio engagement - Khlouf, Mahmoud Mohammad Mustafa; Azmoty, Mohammad Najeeb (Frontiers in Communication, 2025)
IntroductionUniversity radio plays a vital pedagogical and civic engagement role in higher education; however, its alignment with digital-native media behaviors remains underexplored, particularly in the Global South. This study examines undergraduate engagement with university radio in Jordan, focusing on content preferences, access disparities, and institutional broadcasting constraints.MethodsA convergent mixed-methods design was employed, integrating quantitative survey responses from 983 students across three public universities with qualitative interviews from four university radio directors. Although 983 students were initially surveyed, the final analysis was based on 817 valid and analyzable questionnaires. Quantitative data were analyzed using descriptive statistics, t-tests, ANOVA, and effect size estimates (Cohen’s d, η²), while qualitative transcripts were thematically coded following Braun and Clarke’s framework with inter-coder reliability (κ = 0.78).ResultsFindings revealed a strong preference among students for socially oriented, short-form content delivered via digital platforms, with 60% favoring programs under 15 min and 41.9% preferring TikTok. In contrast, directors emphasized traditional FM broadcasting and heritage-driven, state-aligned programming. Significant geographic disparities emerged, with Bedouin students reporting lower engagement levels than their urban peers (ΔM = 1.10, p = 0.003). High satisfaction scores for heritage content (M = 4.15) masked gaps in production capacity due to reliance on volunteer labor.DiscussionThe results underscore a critical misalignment between institutional media practices and student digital consumption patterns, highlighting the need for hybrid, student-led content strategies and targeted infrastructure investments to promote equity and relevance in university broadcasting.